"Trans-nonachlor increases extracellular free fatty acid accumulation and de novo lipogenesis to produce hepatic steatosis in McArdle-RH7777 cells". (August 2018) - Howell, George Eli; McDevitt, Erin; Henein, Lucie; Mulligan, Charlee; Young, Darian
Abstract: Recent studies suggest there may be an environmental exposure component to the development and progression of non-alcoholic fatty liver disease (NAFLD) involving the organochlorine (OC) pesticides or their metabolites. However, the roles of OC compounds in the development of NAFLD has not been fully elucidated. Therefore, the current study was designed to determine if exposure to trans-nonachlor, a prevalent OC compound, could promote hepatocyte lipid accumulation and determine potential pro-steatotic mechanisms. McArdle-RH7777 (McA) hepatoma cells were incubated with trans-nonachlor for 24 h then neutral lipid accumulation was determined by Oil Red O staining. Exposure to trans-nonachlor produced a concentration dependent increase in neutral lipid accumulation. Trans-nonachlor also increased extracellular free fatty acid-induced neutral lipid accumulation which appears to be due at least in part to increased free fatty acid accumulation as evident by increased accumulation of Bodipy labeled dodecanoic acid. Additionally, 14 C-acetate incorporation into total cellular lipids was increased by trans-nonachlor implicating increased de novo lipogenesis (DNL) as a potential mediator of trans-nonachlor-induced neutral lipid accumulation. Taken together, the present data indicate exposure to trans-nonachlor has a direct, pro-steatotic effect on hepatocytes to increase lipid accumulation through the combinatorial actions of extracellular free fatty acid accumulation and increased DNL. Highlights: Trans-nonachlor exposure promotes a concentration dependent increase in neutral lipid accumulation in McArdle-RH7777 cells Extracellular free fatty acid-induced lipid accumulation is increased by trans-nonachlor Exposure to trans-nonachlor significantly increases Bodipy-labeled dodecanoic acid accumulation Trans-nonachlor significantly increases cellular de novo lipogenesis